Hypocrisy and Epistemic Injustice - Carey, Brian (Ethical theory and moral practice, 2024)
In this article I argue that we should understand some forms of hypocritical behaviour in terms of epistemic injustice; a type of injustice in which a person is wronged in their capacity as a knower. If each of us has an interest in knowing what morality requires of us, this can be undermined when hypocritical behaviour distorts our perception of the moral landscape by misrepresenting the demandingness of putative moral obligations. This suggests that a complete theory of the wrongness of hypocrisy must account for hypocrisy as epistemic injustice.